Ingkar Janji dalam Praktik Pengalihan Utang - Nufiar; Nazaruddin (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2021)
This study aims to find out about broken promises in the practice of diversion which is reviewed according to Islamic law and law. The research method used is literature study by studying the Scriptures, the Constitution, the laws and regulations. And data analysis using descriptive methods, namely researching the facts that exist at the moment and reporting what will happen. The results show that breaking promises in the practice of debt transfer is bad behavior that can diminish trust and loyalty to someone, where Not being able to be on time in making debt payments even though when the debt was transferred has canceled it, but what happened is breaking promises in the practice of debt transfer according to Islamic law is not allowed because it is not in accordance with life. A positive legal review of debt transfers often has higher consequences than Islamic law because legally positive debt transfers are defined as an illegal act.